An Examination of Volatility Incremental Effect on the Explanatory Power of Fama and French Three-Factor Model in Tehran’s Stock Exchange - ahmad badri; azim rajabi (راهبرد مدیریت مالی, 2013)
Abstract Many attempts have been made so far to design a proper model to predict stock return. One of the oldest models is CAPM. Despite the relative acceptability, this model is usually criticized for low explanatory power and also due to the results of different experimental examinations. The Fama and French Three-Factor Model (1993) is one of the latest models that is introduced in this field. After introducing this model, many researchers have tried to increase its explanatory power by adding some other factors to it and the most famous of them is The Carhart Four-Factor Model that has added the momentum factor to the Three-Factor Model. Subsequent researches have concentrated on the volatility. This research is conducted on the explanatory power of the four-factor model that by adding volatility has made it the center of attention in Tehran’s Stock Exchange. The sample that is being studied on includes 95 firms in a period between the years 1381 to 1390. The results show that in contrast to the results obtained by Fama and French researches (1993), large firms compared to small ones and growth firms compared to value firms have higher returns. Moreover, firms with higher standard deviation of the return have higher return compared to those with lower standard deviation. Also, adding the volatility factor to the three-factor model results in significant increase in the explanatory power of the three-factor model. Finally, the explanatory power of the four-factor model is not influenced by industry.